Estudos de avaliação e melhoramento de produtos para indústria de petróleo e de bioderivados - Luna, Francisco Murilo Tavares de (2012)
In this work, the methods for evaluation and modification of petroleum-based and bio-based products were studied. In the first part of this study, the adsorption of C8 aromatics in commercial molecular sieves was evaluated. The separation of xylene isomers is an important issue in the petrochemical industry. Headspace and chromatographic pulse techniques were used to measure experimental equilibrium data. This approach is very useful for the selection of adsorbents, as well as in the investigation of selectivity variation, with respect to composition and process temperature. The adsorption selectivities of multicomponent mixtures determined by the chromatographic pulse method were in agreement with the values obtained using headspace technique. The aforementioned values indicate the character of para-selectivity in zeolites Y (αpx/ox ~ 4) and beta (αpx/ox ~ 2), as well as the ortho-selectivity for the mordenite zeolites (αox/px ~ 1.5). In the second part of this study, we studied the adsorption of polyaromatics using model samples and heavy naphthenic oils (HNO). The experiments with model solutions were used to study the capacity of polycyclic aromatic adsorption to evaluate the process parameters and to select the most promising adsorbents (Norit 830W and Norit 1240 Plus), with samples for the evaluation of the HNO. Therefore, the samples were characterized and the HNO had a high content of polyaromatics hydrocarbons (8.2% m/m). Through column experiments, it was possible to evaluate the adsorption capacity of activated carbons, estimating parameters and mass transfers to simulate the breakthrough behavior of the above systems. We evaluated the physicochemical properties and the content of polyaromatics after treatment. The results confirmed the efficiency of activated carbons as an alternative process to reduce polyaromatics content of a HNO. In the third part of this study, we analyzed the physicochemical properties and the oxidation resistance of bio-based products (biodiesel and biolubricants) of the castor oil. Hence, the use of antioxidants increased from 6 to 15 times the stability of castor oil biodiesel. Stability studies of hydrogenated biolubricants with the best antioxidants showed an elevation of the induction period by 10 times.